Solving the capacitated vehicle routing problem with two-dimensional loading constraints using a parallel VNS approach. (12th December 2022) - Sbai, Ines; Krichen, Saoussen; Limam, Olfa
A combination of the two most important problems in logistics called the capacitated vehicle routing problem with two-dimensional loading constraint is studied in this article. It aims in designing the most appropriate pathways, starting and terminating at a central depot, minimising the total transportation cost with a homogenous fleet of vehicles. Items loaded in each vehicle's trip must satisfy the two-dimensional of orthogonal packing constraint. Since the problem is an NP-hard optimisation problem, a large number of approaches have been proposed. Whereas, finding the exact solution via optimisation is still a challenging problem due to their complexity. In order to increase the exploration in the solution space, we propose the parallel variable neighbourhood search algorithm. It is tested with 180 benchmark instances and compared with state-of-the-art approaches. The results showed that our approach is competitive in terms of the quality of solutions found.